HTR-8/SVneo cell line contains a mixed population of cells. (February 2017) - Abou-Kheir, Wassim; Barrak, Joanna; Hadadeh, Ola; Daoud, Georges
Abstract: Introduction: The placenta, a transient organ in humans, is essential for pregnancy maintenance and fetal development. Trophoblast and stromal cells are the main cell types present in human placenta. Trophoblast cells are derivatives of the trophectoderm layer and fulfill the endocrine, exchange, invasion and implantation processes of the placenta, whereas stromal cells are of extraembryonic mesenchymal origin and are important for villous formation and maintenance. Different cell lines were developed to study trophoblast functions including BeWo, JEG-3 and JAR from chorioncarcinoma while HTR-8/SVneo was developed using first trimester extravillous trophoblast infected with simian virus 40 large T antigen (SV40). These cell lines are largely used to study trophoblast functions including cell fusion, migration and invasion. Therefore, the purity of each cell lines is crucial in order to be able to use them as a model recapitulating trophoblast cells. Methods: HTR-8/SVneo, BeWo, JEG-3 and JAR were analyzed for epithelial and mesenchymal markers using immunofluorescence, real time PCR and Western blot. Results: Our results showed that HTR-8/SVneo cell line contains two populations of cells suggesting the presence of trophoblast and stromal/mesenchymal cells. While all cells in BeWo, JEG-3 and Jar are positive for the trophoblast/epithelial marker CK7, HTR-8/SVneo cells contained few clusters of CK7 positive cells. Interestingly, vimentin expression was detected in a subset of HTR-8/SVneo cells and was completely absent from all other tested placental cell lines. Discussion: Our results unveil the presence of a heterogeneous population of trophoblast and stromal cells within HTR-8/SVneo cell line. This mixed population of cells should be taken into consideration when using this cell line to study trophoblast functions. Highlights: HTR-8/SVneo cell line contains epithelial and mesenchymal cells. Vimentin expression in HTR-8/SVneo. Mesenchymal to epithelial transition (MET) during trophoblast formation. Bewo, JEG-3 and Jar cell lines are pure trophoblast cells.